Muscle strength is associated with COVID‐19 hospitalization in adults 50 years of age or older. Issue 5 (6th August 2021) - Cheval, Boris; Sieber, Stefan; Maltagliati, Silvio; Millet, Grégoire P.; Formánek, Tomáš; Chalabaev, Aïna; Cullati, Stéphane; Boisgontier, Matthieu P.
Abstract: Background: Weak muscle strength has been associated with a wide range of adverse health outcomes. Yet, whether individuals with weaker muscle strength are more at risk for hospitalization due to severe COVID‐19 is still unclear. The objective of this study was to investigate the independent association between muscle strength and COVID‐19 hospitalization. Methods: Data from adults 50 years of age or older were analysed using logistic models adjusted for several chronic conditions, body‐mass index, age, and sex. Hand‐grip strength was repeatedly measured between 2004 and 2017 using a handheld dynamometer. COVID‐19 hospitalization during the lockdown was self‐reported in summer 2020 and was used as an indicator of COVID‐19 severity. Results: The study was based on the Survey of Health, Ageing and Retirement in Europe (SHARE) and included 3600 older adults (68.8 ± 8.8 years, 2044 female), among whom 316 were tested positive for the severe acute respiratory syndrome coronavirus 2 (8.8%), and 83 (2.3%) were hospitalized due to COVID‐19. Results showed that higher grip strength was associated with a lower risk of COVID‐19 hospitalization [adjusted odds ratio (OR) per increase of 1 standard deviation in grip strength = 0.64, 95% confidence interval (95% CI) = 0.45–0.87, P = 0.015]. Results also showed that age (OR for a 10 ‐year period = 1.70, 95% CI = 1.32–2.20, P < 0.001) and obesity (OR = 2.01, 95% CI = 1.00–3.69, P = 0.025) were associated with higher risk of COVID‐19 hospitalization. Sensitivity analyses using different measurements of grip strength as well as robustness analyses based on rare‐events logistic regression and a different sample of participants (i.e. COVID‐19 patients) were consistent with the main results. Conclusions: Muscle strength is an independent risk factor for COVID‐19 severity in adults 50 years of age or older.